2021
DOI: 10.12793/tcp.2021.29.e24
|View full text |Cite
|
Sign up to set email alerts
|

Trends of clinical trials from 2017 to 2019 in Korea: an integrated analysis based on the Ministry of Food and Drug Safety (MFDS) and the Clinical Research Information Service (CRIS) registries

Abstract: Public disclosure of approved clinical trials in a reliable registry can provide the transparency of the study. Although the registration of clinical trials has increased remarkably, the integrity of the data is not always satisfactory. In this study, we analyzed public clinical trial databases updated by the Ministry of Food and Drug Safety (MFDS) and Clinical Research Information Service (CRIS) registry to provide an overview of the trends of clinical trials approved between 2017 and 2019 in Korea. Informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…Another consideration for recruitment is geographic accessibility. In our previous study, we found that ~70% of clinical trials in South Korea were conducted in the metropolitan area (Seoul and Gyeonggi‐do) 27 . Similarly, most participants (76.3%) are from the metropolitan area in this study.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Another consideration for recruitment is geographic accessibility. In our previous study, we found that ~70% of clinical trials in South Korea were conducted in the metropolitan area (Seoul and Gyeonggi‐do) 27 . Similarly, most participants (76.3%) are from the metropolitan area in this study.…”
Section: Discussionsupporting
confidence: 56%
“…In our previous study, we found that ~70% of clinical trials in South Korea were conducted in the metropolitan area (Seoul and Gyeonggi-do). 27 Similarly, most participants (76.3%) are from the metropolitan area in this study. However, the proportion of participants from other regions was increased.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation